Migration and development in the 21st century: imperialism and the export of labour force - Delgado Wise, Raúl (Revista Española de Desarrollo y Cooperación, 2023)
It is argued that the relationship between migration and development in contemporary capitalism and imperialism is based on the emergence of a new international division of labour, whose axis is the export of labour power. This export operates in two complementary ways: indirectly, through assembly plants in peripheral countries, and directly, through labour migration. With the profound restructuring that innovation systems are currently undergoing, the export of labour force takes on a broader connotation by incorporating skilled and highly skilled labour force from peripheral countries.